The Power of Proofing Use of Surrogate at The End of The Notary Deal - Mucharoroh Mucharoroh (Sultan Agung Notary Law Review, 2020)
The objectives of this study are to: 1) To determine and analyze the legal strength of the Surrogate at the end of the Notary Deed. 2) To find out and analyze the evidence if there is denial of the Surrogate at the End of the Notary Deed. The approach method in this research is a statute approach, a conceptual approach and a case approach. The research specification used is descriptive analytical, which is to describe the results of the study with data that is as complete and detailed as possible. The data required includes primary data, secondary data and tertiary data that can support the assessment, which is then analyzed using descriptive analysis methods. Based on the results of data analysis, it is concluded that: 1) The power of the Surrogate Law at the end of the Notary Deed has perfect legal power, because based on UUJN, the formal requirements of the Authentic Deed are signatures from the tappers and also the attachment of letters and documents and fingerprints of the tappers on the Minuta Akta Notary is proof of the authenticity of a Deed that has perfect legal force, likewise Surrogate is a substitute for signatures and fingerprints which have the same power as the signature. 2) Evidence that if there is denial of the Surrogate at the end of the Notary Deed, the Notary can deny it by showing that the Deed is in accordance with the procedures and provisions ordered by law, by presenting the witnesses who signed the Deed accompanied by a sheet showing the use of the Surrogate accompanied by an attachment to the Doctor's statement which was stated at the End of the Notary Deed. As for the form of Notary caution in using Surrogate in the Notary Deed so as not to experience denial in the future. Notaries perform all obligations ordered by law. And in the event that there is a denial of the truth of the Surrogate by one of the parties who feels that his/her rights have been harmed which aims to invalidate the Deed, it must be based on a Court Decision which begins with a lawsuit and the responsibility of proving an Authentic Deed on the party arguing or who filed a lawsuit.